2021
DOI: 10.3389/fphys.2021.676265
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Injection of miR-1 Reduces Insulin Resistance in Obese Mice

Abstract: The role of microRNAs in metabolic diseases has been recognized and modulation of them could be a promising strategy to treat obesity and obesity-related diseases. The major purpose of this study was to test the hypothesis that intramuscular miR-1 precursor replacement therapy could improve metabolic parameters of mice fed a high-fat diet. To this end, we first injected miR-1 precursor intramuscularly in high-fat diet-fed mice and evaluated glucose tolerance, insulin sensitivity, and adiposity. miR-1-treated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…According to the order of expression, the top 10 miRNAs were taken from IMF and SCF, respectively ( Supplementary Table 2 ). Among them, miR-26, let-7, miR-27, and miR-1 families play important roles in adipogenic differentiation and lipid metabolism ( 30 , 37 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the order of expression, the top 10 miRNAs were taken from IMF and SCF, respectively ( Supplementary Table 2 ). Among them, miR-26, let-7, miR-27, and miR-1 families play important roles in adipogenic differentiation and lipid metabolism ( 30 , 37 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Russell et al [118] demonstrated that exercise not only upregulates the expression level of myomiRs, but can also increase the expression of miRNA maturation-related proteins such as Drosha, Dicer, and exportin-5. Rodrigues et al [119] demonstrated by skeletal muscle injection of miR-1 that miR-1 overexpression can activate p-AMPK, upregulate PGC-1α and carnitine palmitoyltransferase 1b protein expression, and improve skeletal muscle mitochondrial biogenesis and skeletal muscle oxidative metabolism. Nie et al [101] demonstrated that 6 weeks of endurance exercise increased the level of miR-133a and increased the expression of the mitochondrial biogenesis regulators PGC-1α, peroxisome proliferative activated receptor gamma coactivator-1β (PGC-1β), NRF1, and TFAM in skeletal muscle of wild-type mice, followed by upregulation of mitochondrial biogenesis.…”
Section: Exercise-induced Alterations In Mirna Expressionmentioning
confidence: 99%
“…Lipid compositions in exosomes, which are commonly enriched with cholesterol and sphingomyelin, and minimal amounts of lecithin and phosphatidylethanolamine, primarily depend on exosome-producing cells [58][59][60][61][62]. Furthermore, it has been revealed that lean mice become insulin resistant due to the administration of exosomes isolated from the feces of obese mice that were fed a high-fat diet (HFD) and of type II diabetic patients [63][64][65]. An HFD alters the lipid composition of exosomes [63].…”
Section: Proteins Peptides Lipid and Nucleic Acids In Exosomesmentioning
confidence: 99%